DRUG UTILIZATION STUDY OF BENZODIAZEPINES BASED ON WHO CORE DRUG USE INDICATORS IN AN OUTPATIENT DEPARTMENT OF A TERTIARY CARE HOSPITAL IN EASTERN UTTAR PRADESH, INDIA - RAI, JAYANT; AMBU PANDEY; JAMAL HAIDER; MISHRA, SHASHANK SHEKHAR (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: To analyse the drug utilization pattern of the benzodiazepines being prescribed at our hospital by calculating various parameters defined by World Health Organization as core drug use indicators. Methods: This cross-sectional study has enrolled 388 patients receiving one drug from benzodiazepine group coming to the out-patient department of dept. of Psychiatry in a tertiary care hospital in eastern Uttar Pradesh. Drug consumption pattern of benzodiazepines was analysed by calculating defined daily dose (DDD) per 1000 inhabitants per day, Prescribed daily dose (PDD) and the PDD to DDD ratio. Results: Out of 388 patients enrolled in the study, mostly subjects were females. Regarding age group, most of the study participants belongs to 30-40 years age group followed by 18-30 years. Most of the participants were suffering from depression with anxiety followed by anxiety alone. Most commonly prescribed medicine in this study was clonazepam followed by lorazepam. PDD/DDD ratio of all the prescribed benzodiazepines in this study was less than 1. Conclusion: This study concludes that the prescribed benzodiazepines were appropriate for their indications and the prescribed daily dose and its ratio with defined daily dose reflects appropriate utilization of benzodiazepines for its indication.